(untitled) (Advancements in Homeopathic Research, 2022)
Translational Research is a bench to bedside approach in which knowledge of basic sciences and clinical research is applied to develop the techniques specially designed to improve health outcomes, which benefit the community Health system. In India, the Translation Health Science and Technology Institute (THSTI), Department of Biotechnology, Ministry of science and technology, is working for the promotion of Translational research. The relevance of Translational research in public health is very important is regarding health disparity, bridging the gap between health practice and health performance, increasing the partnership catalyst among different agencies, and developing patient-oriented research Programs. Translational research can be explained by the help of the T Spectrum (Translational spectrum) in which different stages of Translation form the entire process of Translational Research. Hahnemannian concept of remedy reaction is not clear, which makes homoeopathy debatable in the medical fraternity. Homeopathy research is done in domains like drug standardization, drug proving, clinical verification, fundamental research, and literacy research which need to be well integrated with the subjects of teaching and related allied sciences. It will help homeopathy to develop the scientific basis to face the skepticism.In our Country, the field of translational research is in the era of childhood. There is a strong need of developing a curriculum for Translational medicine and research, which benefits the need for medical science including the Indian system of medicine and homeopathy. By this, the students of related medical practices will learn to solve the health problems of the community, thereby making education more practical for the current health care delivery system. As translational research is by directional, it is challenging to develop training programs of translational research in homoeopathy as each trainee should be a master of combined skills that are not taught in traditional training programs in homoeopathic education. For this, different regulatory bodies should play their part and work effectively to discuss the problems arises and solves them effectively. The development of translational medicines must start from ground level so that the scientific methods adopted will help homoeopathy to offer a lot to community health.